Trace Elements in Some Hazelnut Varieties Near Industrial Area and Far From Industrial Area in Turkey - Beyhan, O.; Elmastas, M.; Genc, N. (Asian Journal of Chemistry, 2010)
The aim of this work is to compare the Cu, Mn, Ni, Co, Fe, Zn contents of three native Turkish hazelnut varieties (Karayagli, Yomra and Delisava) near industrial area and far from industrial area. Trace element contents were determined by a flame and graphite furnace atomic absorption spectrometry technique after wet-digestion. The results according to this study showed that Mn and Co concentrations in the hazelnut in industrrial area and far from industrial area were generally correlated with the degree of trace element contamination of the environment. Other elements Cu, Ni, Fe and Zn were generally not correlated with the degree of trace element of the environment.